TRUMP POLICY: NORTH KOREA'S NUCLEAR DEVELOPMENTS IN AN HISTORICAL FRAMEWORK - Wulandari, Nuryuana Dwi; Agung, Rendi Marta (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2025)
North Korea is a country located in the East Asia region. North Korea is one of the countries that is developing nuclear. The development of nuclear power has become a problem of security stability in the East Asia region and its surroundings, causing strong criticism from several countries such as the United States and even the UN Security Council. The purpose of this study is to find out 1) The relationship between North Korea and the United States in history; 2) The policies of the United States government before Trump; 3) The policies of the Trump government to stabilize the East Asia region. This study uses a historical approach to literature study. The results of the research discussion 1) North Korea is a country that was formed as a result of World War II. The Korean War sparked because of the dispute between the United States (South Korea) and the Soviet Union (North Korea) there was no peace but the two countries made a ceasefire agreement; 2) Before Trump became president, previous presidents had policies to reduce the nuclear power owned by North Korea such as President Clinton with the agreed framework, President George W Bush with the Six-Party Talks, President Barack Obama with "Strategic Patience"; 3) During the Donald Trump administration, the policy through Trump's harsh criticism speech to North Korea, Maximum pressure and high-level diplomacy became one of the policies issued by Trump. In addition, Trump also conducted High-Level Diplomacy Trump met directly with the North Korean government Kim Jong-un to reduce North Korea's nuclear.